Pengaruh Kualitas Pelayanan Fiskus, Pemahaman Peraturan Perpajakan Dan Penerapan Sistem E-Filling Terhadap Kepatuhan Wajib Pajak: Sosialisasi Perpajakan Sebagai Pemoderasi - Devi Safitri; Sem Paulus Silalahi (ITB AAS INDONESIA, 2020)
This research is aimed to examine empirically effect of fiscus service quality, tax regulation comprehension, and e-filing system implementation on Small Medium Enterprises (SMEs) Personal Taxpayer obedience, with taxation socialization as moderating variable. Research samples are Personal SMEs registered in Tax Service Office (Kantor Pelayanan Pajak) Pratama Pekanbaru Senapelan. Sampling method uses purposive sampling, and sample size measured by Slovin formula. Analysis method uses Multiple Regression Analysis and Moderated Regression Analysis (MRA). Result of research shows that fiscus service quality and e-filing system implementation have no effect on taxpayer obedience partially, while tax regulation comprehension has significant effect on taxpayer obedience. Further, taxation socialization is failed to moderates the effect of fiscus service quality on taxpayer obedience. Taxation socialization is failed as well to moderates the effect of tax regulation comprehension on taxpayer obedience, and taxation socialization is failed to moderates the effect of and e-filing system implementation on taxpayer obedience.